Simultaneous determination of chromium and nickel in medicinal plants by slurry sampling graphite furnace atomic absorption spectrometry - Fortunato, Felipe Manfroi [UNESP]; Miranda, Kelber dos Anjos de [UNESP]; Gomes Neto, José Anchieta [UNESP]; Freschi, Gian Paulo Giovanni (My University, 2013)
Slurry sampling graphite furnace atomic absorption spectrometry was employed for the simultaneous determination of Cr and Ni in medicinal plants. A chemical modifi er was not required and the optimum pyrolysis and atomization temperatures were 1600 °C and 2300 °C, respectively. Calibration using aqueous standards allowed accurate and precise results. Characteristic masses for Cr and Ni were 5.8 and 31 pg, respectively. The limits of detection obtained were 0.04 μg g−1 for Cr and 0.3 μg g−1 for Ni using 0.5% (m/v) slurries (100 mg/20 mL). Relative standard deviations of 3 measurements for Cr and Ni in medicinal plant slurries were below 10%. Accuracy was evaluated after analyzing the standard reference materials Tomato Leaves (1573a), Apple Leaves (1515), Pine Needles (1575a) and Peach Leaves (1547). The results obtained were in agreement with certifi ed values at a 95% confi dence level (unpaired t-test). The proposed method was applied to slurries of ten medicinal plant samples and the concentrations varied from 1.76 to 11.6 μg g-1 for Cr and from 1.2 to 5.5 μg g-1 for Ni. The lifetime of the graphite atomizer was around 600 fi rings.
Keywords: Crômio; Níquel; plantas medicinais; Suspensão; GF AAS; Chromium; Nickel; Medicinal plants; Slurry sampling; Graphite furnace atomic absorption spectrometry